2013
DOI: 10.3389/fcimb.2013.00108
|View full text |Cite
|
Sign up to set email alerts
|

Competition for zinc binding in the host-pathogen interaction

Abstract: Due to its favorable chemical properties, zinc is used as a structural or catalytic cofactor in a very large number of proteins. Despite the apparent abundance of this metal in all cell types, the intracellular pool of loosely bound zinc ions available for biological exchanges is in the picomolar range and nearly all zinc is tightly bound to proteins. In addition, to limit bacterial growth, some zinc-sequestering proteins are produced by eukaryotic hosts in response to infections. Therefore, to grow and multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
82
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 98 publications
(110 reference statements)
3
82
0
Order By: Relevance
“…For example, zinc is an essential cofactor for enzymatic reactions, DNA synthesis, and gene expression (2). One study has shown that over 3% of Escherichia coli proteins contain zinc (3).…”
mentioning
confidence: 99%
“…For example, zinc is an essential cofactor for enzymatic reactions, DNA synthesis, and gene expression (2). One study has shown that over 3% of Escherichia coli proteins contain zinc (3).…”
mentioning
confidence: 99%
“…Over the course of infection, M. tuberculosis can exist in various environments and thus is exposed to a wide range of metals (39)(40)(41). In order to determine whether iron-and zinc-mediated regulation of EsxG and EsxH might influence virulence, we infected murine BMDMs with M. tuberculosis that was pregrown for 3 days in Sauton's medium with iron and zinc or without iron and zinc to test conditions that maximize the difference in EsxG-EsxH secretion.…”
Section: Resultsmentioning
confidence: 99%
“…Staats et al (2013) present the role of Zn in bacteria-host relationship and how this metal represents a very promising target for the development of novel antimicrobial strategies. Cerasi et al (2013) emphasize the role of Zn in the host-fungi relationships and the impact of Zn bioavailability on the expression of virulence genes.…”
Section: Microbial Adaptation To Host Defenses: Metallo-transporters mentioning
confidence: 99%
“…Staats et al (2013) present the role of Zn in bacteria-host relationship and how this metal represents a very promising target for the development of novel antimicrobial strategies. Cerasi et al (2013) emphasize the role of Zn in the host-fungi relationships and the impact of Zn bioavailability on the expression of virulence genes.Lastly, metallo-regulation of bacterial gene expression is discussed in relation to virulence. Porcheron et al (2013) review the enterobacterial metallo-transporters and their regulation, discussing strain-specific differences.…”
mentioning
confidence: 99%